1999
DOI: 10.1128/aac.43.1.178
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of 914 Beta-Hemolytic Streptococci Isolated from Pharyngeal Swabs in Spain: Results of a 1-Year (1996–1997) Multicenter Surveillance Study

Abstract: A nationwide susceptibility surveillance study of beta-hemolytic streptococcal isolates from pharyngeal swabs obtained in 11 Spanish hospitals between May 1996 and April 1997 against 12 antibiotics was carried out. Of the isolates 86% (786 of 914 isolates) were group A and 8.4% (77 of 914 isolates) were group C. No resistance was found to β-lactam antibiotics, but significant differences (P< 0.001) with respect to lack of susceptibility to macrolides were found between groups (27% for group A and 12% for gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 14 publications
0
22
0
3
Order By: Relevance
“…Barry et al [25] noted that 8% of 764 S. pyogenes isolates from the United States had MICs of ciprofloxacin of у2 mg/mL; 2 isolates had off-scale MICs of 14 mg/mL. Baquero et al [5] also reported a small portion of isolates (!10%) with MICs of ciprofloxacin of 2-4 mg/mL among 786 pharyngeal isolates of S. pyogenes from Spain.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Barry et al [25] noted that 8% of 764 S. pyogenes isolates from the United States had MICs of ciprofloxacin of у2 mg/mL; 2 isolates had off-scale MICs of 14 mg/mL. Baquero et al [5] also reported a small portion of isolates (!10%) with MICs of ciprofloxacin of 2-4 mg/mL among 786 pharyngeal isolates of S. pyogenes from Spain.…”
Section: Methodsmentioning
confidence: 95%
“…There has been concern about the emergence of macrolide resistance in this organism, with high rates reported in a number of countries, including Finland [1], Italy [2,3], Taiwan [4], and Spain [3,5]. Surveillance data from the United States suggest a low level of macrolide resistance among S. pyogenes (!3%) [6], but a clonal outbreak of infection with an erythromycin-resistant strain in Pittsburgh was recently documented [7].…”
mentioning
confidence: 99%
“…Macrolide resistance has increased in S. pneumoniae dramatically to an overall prevalence of 22% and is exceeding penicillin resistance in many countries [3,6]. Increased levels of erythromycin resistance in GAS have been reported especially for European countries like Finland, Italy, Hungary, Austria and Spain [3,[7][8][9][10][11]. In addition, frequent failure to eradicate H. influenzae is observed in pediatric patients treated with macrolides and azalides for acute otitis media, even though clinical isolates are still reported susceptible in vitro according to current National Committee for Clinical Laboratory Standards (NCCLS) definitions [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…17 '35 Erythromycin is a suitable alternative for patients who are allergic to penicillin.4 In some countries, including Portugal, this antibiotic and other newer macrolides such as clarithromycin, roxithromycin, and azithromycin are now extensively used in the treatment of pharyngitis and other upper respiratory tract infections because they are safe, effective, and can be administered orally. Significant rates of macrolide resistance have been documented in Japan, 21,22'36 United Kingdom,25 Australia, 30 Finland, 18,27,28 Sweden,15 Austria,20 Taiwan,14 and California in the United States,37 although in most countries of the world rates of resistance are less than 5% among S. pyogenes?1 However, during the last decade, increasing prevalence of resistance has also been reported from southern European countries, including Italy5, 7,9 and Spain.1, 10,24 Two mechanisms of resistance to macrolide antibiotics have been described in 5. pyogenes31: (1) the MLSrj phenotype, which results from a target site modification occurring at the level of the ribosomes via an erm (erythromycin resistance methylase) gene, rendering the strain resistant to most macrolides, lincosamides, and streptogramin B compounds (expression of MLSB resistance can be inducible or constitutive31);…”
Section: Introductionmentioning
confidence: 99%